The oncogenic neurotrophin receptor tropomyosin-related kinase variant, TrkAIII - Antonietta Rosella Farina; Lucia Cappabianca; Pierdomenico Ruggeri; Luciana Gneo; Cristina Pellegrini; Maria-Concetta Fargnoli; Andrew Reay Mackay (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Oncogenes derived from the neurotrophin receptor tropomyosin-related kinase TrkA act as drivers in sub-populations of a wide-range of human cancers. This, combined with a recent report that both adult and childhood cancers driven by novel oncogenic TrkA chimeric-fusions exhibit profound, long-lived therapeutic responses to the Trk inhibitor Larotrectinib, highlights the need to improve clinical detection of TrkA oncogene-driven cancers in order to maximise this novel therapeutic potential. Cancers potentially driven by TrkA oncogenes include a proportion of paediatric neuroblastomas (NBs) that express the alternative TrkA splice variant TrkAIII, which exhibits exon 6, 7 and 9 skipping and oncogenic-activity that depends upon deletion of the extracellular D4 Ig-like domain. In contrast to fully spliced TrkA, which exhibits tumour suppressor activity in NB and associates with good prognosis, TrkAIII associates with advanced stage metastatic disease, post therapeutic relapse and worse prognosis, induces malignant transformation of NIH-3T3 cells and exhibits oncogenic activity in NB models. TrkAIII induction in NB cells is stress-regulated by conditions that mimic hypoxia or perturbate the ER with potential to change TrkA tumour-suppressing signals into oncogenic TrkAIII signals within the stressful tumour microenvironment. In contrast to cell surface TrkA, TrkAIII re-localises to intracellular pre-Golgi membranes, centrosomes and mitochondria, within which it exhibits spontaneous ligand-independent activation, triggering a variety of mechanisms that promote tumorigenicity and malignant behaviour, which impact the majority of cancer hallmarks. In this review, we present updates on TrkAIII detection and association with human malignancies, the multiple ways TrkAIII exerts oncogenic activity and potential therapeutic approaches for TrkAIII expressing cancers, with particular reference to NB.